KAJIAN PSIKO-PASTORAL TENTANG TUGAS PENATUA DAN DIAKEN GEREJA - Maurits J Polattu (IAKN Ambon, 2018)
Church services now require servants such as elders and deacons who are professional and responsible for service. Elders and Deacons in the church today, many do not understand their duties. For them, Elders and Deacons are only ecclesiastical offices that elevate social status in the church and society. In fact, many elders and deacons do not understand their duties so that they are only limited to the task of program routines without understanding the purpose and meaning of the services performed. Therefore, Deacon Elders must be aware that the service they are doing is pastoral. Every service carried out must be based on theological thinking about pastoralism in one way, namely pastoral counseling. Elders and Deacons must carry out pastoral functions in their lives. Pastoral visits must be carried out maximally so that the process of counseling or pastoral care can be carried out as a service assignment for Elders and Deacons.